The dynamics of political myths and ideologies - Thomas Apolte; Julia Müller (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2019)
Why do groups of even well-educated individuals sometimes persistently believe in political myths and ideologies? We follow cognition psychology in its finding that individuals sometimes stick with intuitive but false propositions. We also follow Kahneman, however, in maintaining that they challenge their intuition when the consequences for their individual wealth are sufficiently high. We embed these propositions into a model that determines the conditions of a myth equilibrium, in which almost all individuals stick with ex-post rationalization to justify their initial intuition, or a truth equilibrium in which all individuals pursue ex-ante reasoning that aims to get as close to the truth as possible. We show why myths are clustered around certain groups and why groups are more likely to stick with political myths than individuals, thus disproving Condorcet's jury theorem.
Keywords: D72; D83; D91; 330; Cognition; Ideology; Rational Ignorance